Prevalência e fatores de risco de Ascaridideos e outros geohelmintos no solo de Uberlândia, Minas Gerais, Brasil - Mota, Kelem Cristina Pereira (2015)
Geohelminths are parasites which realize part of their life cycle on the soil, where the eggs become embryos and the larvae are then viable, thus being able to infect the host. Among the geohelminths, parasites from the Ascarididea family have a significant role in the public and veterinary health. This paper aimed at determining the prevalence of Ascarididea on the soil in different areas located in a town in the State of Minas Gerais, Brazil. The study was developed in squares, parks, sports clubs, orchards and children s education city schools (EMEIs). The samples of sand/soil/grass were collected from January to August 2014, within the different areas. On each site four lateral samples, as in a quadrant, were collected, and a central sample, thus forming a homogenous pool. The above cited samples were bagged, tagged and transported to the Parasitological Laboratory of the Federal University of Uberlândia (UFU) in order to be processed. The microscope screening was performed through the sedimentation techniques of formolether and spontaneous to observe the evolutionary forms. Of the 183 collected samples, eight (4,4%) belonged to parks, 16 (8,7%) sports clubs, 76 (41,5%) squares, 23 (12,6%) orchards and 60 (32,8%) EMEIs. Of the total, 28 (15,3%) contained eggs of Ascarididea. Higher levels of positivity were demonstrated in the raining season (25,0%), in samples collected in the southern region of the town (25,1%), on ground soils (27,3%). 23 (12,6%) were detected through the formol-ether technique and 10 (5,5%) through spontaneous sedimentation. No agreement between the methods was observed from the application of the kappa index, with values of p<0,05 considered significant. It was, therefore, concluded that the soils in the town of Uberlândia are contaminated with eggs and larvae of geohelminths, making it possible the dissemination of illnesses among animals and humans. The formol-ether technique has become the most relevant for the detection of such parasites. Ground soils with rain are considered risk factors to the presence and survival of these parasites.